Multimodal molecular imaging of integrin avb3 for in vivo detection of pancreatic cancer - Trajkovic-Arsic, Marija; Mohajerani, Pouyan; Sarantopoulos, Athanasios; Kalideris, Evdokia; Steiger, Katja; Esposito, Irene; Ma, Xiaopeng; Themelis, George; Burton, Neal; Michalski, Christoph W.; Kleeff, Joerg; Stangl, Stefan; et al. (Journal of Nuclear Medicine, 2014)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease. Late detection of then nonresectable or metastasized tumors emphasizes the need for novel imaging approaches. Here, we report on so far nonexploited potentials of αvβ3 integrin-targeted molecular imaging technologies for detection of PDAC using genetically engineered mouse models. Methods: Immunohistochemistry and Western blot were used for characterization of αvβ3 expression in murine and human PDAC.We applied IntegriSense 680 fluorescencemolecular tomography, intraoperative fluorescence imaging, and 68Ga-NODAGA-RGD PET for αvβ3 integrin molecular in vivo imaging of spontaneous PDAC occurring in Ptf1a+/Cre;Kras +/LSL-G12D;p53LoxP/LoxP mice. (NODAGA is 1,4,7-triazacyclononane- 1,4-bis[acetic acid]-7-[2-glutaric acid] and RGD is arginine- glycine-aspartic acid.) Results: αvβ3 integrin is expressed in tumor cells of human and murine PDAC. IntegriSense fluorescence molecular tomography and 68Ga-NODAGA-RGD PET enabled faithful visualization of PDAC. Furthermore, intraoperative optical imaging with IntegriSense 680 allowed good delineation of tumor borders. Conclusion: Imaging approaches targeting αvβ3 integrin expand the potential of molecular imaging for identification of αvβ3-positive PDAC with potential implications in early detection, fluorescenceguided surgery, and therapy monitoring. © 2014 by the Society of Nuclear Medicine and Molecular Imaging, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Fluorescence molecular tomography; Genetically engineered mice; Pancreatic cancer; Positron emission tomography